Favouritism Behaviours of School Administrators: Teachers’ Perceptions of the Secondary Schools in Turkey - Abidin Dağlı; Zühal Akyol (Dinamika Ilmu, 2021)
This study aims to determine favouritism behaviors of school administrators according to public secondary school teachers’ perceptions in terms of some variables. The sample of the study consisted of 22 schools selected randomly from the population and 376 teachers employed in these schools. “Favoritism in the School Management Scale" was used in this research. In the study, teachers stated that favouritism behaviors in their schools are at the "sometimes" level. According to perceptions of teachers, the highest three items in the favouritism scale are: "(1) In the preparation of teachers' weekly lesson plan ( =3,30; Sometimes)", "(2) In the planning of lesson distribution ( =3,12; Sometimes)", "(3) Taking into consideration the complaints of teachers ( =3,08; Sometimes)". The lowest three items in the favouritism scale are: (1) Among the teachers in their hometowns ( =2,14; Rarely); (2) Related to the branches of the teachers ( =2,38; Rarely) and (3) Related to the gender of the teachers ( =2,43; Rarely). No significant difference was detected with respect to the teachers' educational background, gender, marital status, professional experience, and union on the perceptions of favouritism behaviours. Nevertheless, a significant difference was found in all dimensions and throughout the whole scale of favouritism regarding to school size (the number of teachers) variable.